Unitary permeability of gap junction channels to second messengers measured by FRET microscopy. - Hernandez, V; Bortolozzi, M; Pertegato, V; Beltramello, M; Giarin, M; Zaccolo, M; Pantano, S; Mammano, F (2007)
Gap junction channels assembled from connexin protein subunits mediate intercellular transfer of ions and metabolites. Impaired channel function is implicated in several hereditary human diseases. In particular, defective permeation of cAMP or inositol-1,4,5-trisphosphate (InsP(3)) through connexin channels is associated with peripheral neuropathies and deafness, respectively. Here we present a method to estimate the permeability of single gap junction channels to second messengers. Using HeLa cells that overexpressed wild-type human connexin 26 (HCx26wt) as a model system, we combined measurements of junctional conductance and fluorescence resonance energy transfer (FRET) emission ratio of biosensors selective for cAMP and InsP(3). The unitary permeabilities to cAMP (47 x 10(-3) +/- 15 x 10(-3) microm(3)/s) and InsP(3) (60 x 10(-3) +/- 12 x 10(-3) microm(3)/s) were similar, but substantially larger than the unitary permeability to lucifer yellow (LY; 7 +/- 3 x 10(-3) microm(3)/s), an exogenous tracer. This method permits quantification of defects of metabolic coupling and can be used to investigate interdependence of intercellular diffusion and cross-talk between diverse signaling pathways.